Effect of structural defects, surface roughness on sensing properties of Al doped ZnO thin films deposited by chemical spray pyrolysis technique. Issue 4 (March 2017) - Kumar, Manjeet; Singh, Bikmramjeet; Yadav, Pankaj; Bhatt, Vishwa; Kumar, Manoj; Singh, Kulwinder; Abhyankar, A.C.; Kumar, Akshay; Yun, Ju-Hyung
Abstract: In this article, the gas sensing properties of Al-doped ZnO thin films have been reported where the nanocrystalline ZnO based thin films were well deposited by a simple and inexpensive 'chemical spray pyrolysis (CSP)' technique. Films have been found to be uniform, pinhole free and well adherent to the substrate. The morphology, structures, and surface roughness of the deposited Al-doped ZnO thin films were studied by various types of characterization techniques. In addition, the authors have observed that the sensor response and selectivity towards CO gas is improved by the Al doping at a low operating temperature. XRD results showed that the obtained films are nanocrystalline in nature with hexagonal wurtzite phase. Further, the annealed films were used for detection of CO in the air and maximum response was observed at 175 °C. The improvement in sensor response of Al-doped ZnO thin films to CO gas attributed to the defect chemistry, crystallite size and surface roughness.